Characterization of the Calibration Results of Glass Electrode pH-meters using Buffer Solutions Certified by Different Producers - Shehata, Adel B.; AlAskar, Abdurrahman R.; Aldosari, Rashed A.; AlMutairi, Fahad R. (European Journal of Applied Sciences, 2023)
The buffer solutions of pH 4, 7 and 10 are very important certified reference materials in determining the accuracy of pH-meters with glass electrodes. The Saudi SASO/NMCC has certified a set of buffer solutions and their performance in the calibration of pH-meters has been verified with regard to the calibration results by three sets of buffer solutions certified by the Slovak SMU. The strength of traceability, bias, residuals, variance and regression of the calibration results have been characterized in order to evaluate the extent of performance agreement of the buffers from the two producing NMIs. The calibration results of four pH-meters by the four sets of buffer solutions fulfilled the traceability criterion and showed no bias. The regression analysis of the means of pH4, 7 and 10 values revealed that there is no significant difference between these means. Details of these evaluations are described in this article.